A Saudi slave ([S.l. ] Channel 4 Dispatches, 1996)
"Documents the harrowing experiences of a Philippine woman working as a foreign domestic in Saudi Arabia. In this program a British crew follows the story of Jessica, a young Filipino woman, who travels to Saudi Arabia. She wants to work there so that she can raise money for an operation for her daughter who needs heart surgery. Hidden cameras follow her life as she moves from family to family, is raped, beaten and forced to change her religion."
DVD.
Keywords: Women household employees -- Saudi Arabia; Women domestics -- Saudi Arabia; Documentary films